Spectrophotometric Determination of Cu(II) in Analytical Sample Using a New Chromogenic Reagent (HPEDN) - Esraa Raafid; Muneer A. Al-Da’amy; Salih Hadi Kadhim (Indonesian Journal of Chemistry, 2020)
The sensitive, accurate and rapid spectrophotometric method that can be used for determination of Cu(II) in the analytical samples using a new chromogenic reagent azo-Schiff base 1-((4-(1-(2-hydroxyphenylimino)ethyl)-phenyl)diazenyl) naphthalene-2-ol (HPEDN). The synthesized new (azo-Schiff base) ligand was complexed with copper(II) and characterized using UV/Vis spectroscopy, IR spectra, 1H-NMR, 13CN-MR spectra, Molar electrical connectivity, and measuring of their melting points. Then obtained complex showed a brown color with maximum absorption at λmax = 500 nm at pH = 9. Beer’s law is obeyed in the concentration in the range of 1.7 to 5.4 μg/mL. The molar absorption and Sandell’s sensitivity values of Cu(II) complex were found to be 0.5038 × 104 L mol–1 cm–1 and 0.0039 μg cm–2, respectively. Structure of the prepared complex was investigated by using the continuous variation, mole ratio method and slope analysis method. The obtained results showed that the complex has (1:2) (M:L) molar ratio and these results showed that this method were more sensitive, more precise and accuracy through the calculation of (Re, Erel, R.S.D)%. The most important interferences were due to, Co2+, Cd2+, Zn2+, Ni2+, Mn2+, Pd2+, Fe3+ and these were studied, and suitable masking agents were used. This method was applied for the determination of Cu(II) in alloy. The obtained results were compared with flame atomic absorption spectrometry method and these results were in a good agreement in these two cases.